Analysis of The Relationship between Oil Revenues and Bank ‎Credit in Iraq - Wahid , Maysam Salim Abdul; Al-Dulaimi , Dr. Haidar Ali (International Journal of Accounting and Economics Studies, 2025)
Oil constitutes the primary source of public revenue in Iraq, accounting for more than 90% of total government income. This heavy reliance ‎on oil renders the Iraqi economy highly susceptible to fluctuations in global oil markets. Such dependence has had adverse effects on vari-‎ous economic sectors, particularly the banking sector, which plays a critical role in supporting economic activity and providing necessary ‎financing.‎This study aims to examine the impact of oil revenue fluctuations on bank credit in Iraq during the period 2004–2023. The research analyzes ‎the relationship between oil revenues and credit activity through a three-part structure: the first section discusses the concept and volatility of ‎oil revenues; the second explores the nature and significance of bank credit; and the third analyzes the relationship between oil revenues and ‎bank credit in the Iraqi context‎.